Post-streptococcal scleredema an unusual rare mimicker of scleroderma: a case report - F.I. Gorial; N.I. Awadh; A.D. Al-Obaidi; M.N. Al-Obaidi; H.T. Hashim; H.J. Hasan (PAGEPress Publications, 2023)
cleredema of Buschke is a rare pathological disorder of connective tissue, which is characterized by a woody, diffuse induration of the skin, most often in the upper extremities. We report an extremely rare complication of post-streptococcal infection in a six-year-old male complaining of gradually progressing, painless skin thickening and tightness which was preceded by a one-month history of fever, cough, and tonsillitis. By reporting this case, we hope to contribute to the creation of a database for future research aimed at better understanding the incidence, pathophysiology, and management of this extremely rare complication.